Hypoxia-induced predation refuge for northern quahogs (Mercenaria mercenaria) in a temperate estuary. (5th February 2022) - Galligan, Bryan P.; Stuart, Yoel E.; McManus, M. Conor; Stoffel, Heather E.
Abstract: Oxygen depletion in estuaries and coastal waters is often associated with reduced biodiversity, coastal dead zones, and the loss of important ecosystem services. However, some species can benefit from low oxygen conditions due to the indirect effects these conditions have on trophic relationships. In Narragansett Bay, Rhode Island, U.S.A., northern quahogs ( Mercenaria mercenaria ) reach their highest densities in the areas of the Bay most prone to oxygen depletion. One line of evidence suggests that suboxic events (hypoxia and anoxia) can aid quahogs by excluding predators. Here, we analyze data from long-term surveys of water quality and quahog abundances to test whether a hypoxia-induced predation refuge is strong enough to explain quahog population dynamics in Narragansett Bay. We found that quahog cohorts were larger when they had been exposed to low oxygen conditions as juveniles, consistent with the predation refuge hypothesis. However, cohort size was also strongly associated with location and year settled, suggesting that a predation refuge is but one of a suite of factors influencing M. mercenaria populations. Highlights: Hypoxia-Induced Predation Refuge for Northern Quahogs ( Mercenaria mercenaria (Linnaeus, 1758)) in a North Temperate Estuary. Northern quahogs reach high densities in low oxygen areas of Narragansett Bay. Hypoxic events provide quahogs with refugia from epibenthic predators. Quahog cohort size increases when exposed to hypoxia as juveniles. As water quality continues to improve, quahogs may experience increased predation.